Negative ion mass spectrum from observations by the Negative Ion at the Lunar Surface (NILS) instrument onboard of the Chang'E-6 lunar lander. - Wieser, Martin; Zhang, Aibing (Swedish Institute of Space Physics, 2025)
Mass resolved energy-time spectrogram of negatively charged particles recorded on the lunar surface by the Negative Ions at the Lunar Surface (NILS) instrument on Chang'E-6. The data set contains raw detected counts summed over all surface pointing viewing directions.

Massupplöst energi-tids-spektrogram av negativt laddade partiklar registrerade på månytan av instrumentet Negative Ions at the Lunar Surface (NILS) på Chang'E-6. Datauppsättningen innehåller detekterade partiklar summerade över alla tittriktningar som pekar mot månens yta.
Negative ion mass spectrum from observations by the Negative Ion at the Lunar Surface (NILS) instrument onboard of the Chang'E-6 lunar lander.
Keywords: space research; rymdforskning; solar wind; solvind; moon research; månforskning; surfaces; ytor; Chang’E-6; Chang’E-6; negative ion; negativ jon; Fusion, Plasma and Space Physics; Fusion, plasma och rymdfysik